Gartner’s Duct Cyst of the Vagina: A Case Report - Thapa, Baburam Dixit (JNMA J Nepal Med Assoc, 2020)
Paramesonephric duct or Mullerian ducts forms female genital organs whereas mesonephric duct forms male genital organs. The remnant of the mesonephric duct or Wolffian duct in females sometimes forms a mesonephric cyst or Gartner's duct cyst. They are usually asymptomatic and <2 cm but sometimes can be bigger. It is diagnosed with pelvic examination. It is treated with surgical excision of the cyst. This is a unique case in urogynecology as it confuses with pelvic organ prolapse and the mode of treatment is completely different. We report a case of 32-years old lady who presented in urogynecology outpatient department with complain of pelvic organ prolapse. After examination she was diagnosed as vaginal cyst and excision was done and confirmed as Gartners cyst in histopathological examination.